Osteoporosis, need for paradigm sit in Nepal health policy - Kattel, V.; Regmi, N.; Limbu, A.; Pradhan, B.; Maskey, R. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
No abstract available.